2013
DOI: 10.1038/ismej.2013.32
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution SAR11 ecotype dynamics at the Bermuda Atlantic Time-series Study site by phylogenetic placement of pyrosequences

Abstract: Advances in next-generation sequencing technologies are providing longer nucleotide sequence reads that contain more information about phylogenetic relationships. We sought to use this information to understand the evolution and ecology of bacterioplankton at our long-term study site in the Western Sargasso Sea. A bioinformatics pipeline called PhyloAssigner was developed to align pyrosequencing reads to a reference multiple sequence alignment of 16S ribosomal RNA (rRNA) genes and assign them phylogenetic posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
261
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 175 publications
(296 citation statements)
references
References 54 publications
32
261
3
Order By: Relevance
“…1A, Table 1). DMSP lyase enzymes are distributed among multiple protein 1 families, but all lead to the production of DMS and either acrylate (DddL,P,Q,W,Y) or 3-2 hydroxypropionate (3-HP; DddD) 9 . The HTCC1062 genome encodes annotated genes for all 3 steps in the degradation of acrylate to propionyl-CoA or acetyl-CoA (Fig.…”
mentioning
confidence: 99%
“…1A, Table 1). DMSP lyase enzymes are distributed among multiple protein 1 families, but all lead to the production of DMS and either acrylate (DddL,P,Q,W,Y) or 3-2 hydroxypropionate (3-HP; DddD) 9 . The HTCC1062 genome encodes annotated genes for all 3 steps in the degradation of acrylate to propionyl-CoA or acetyl-CoA (Fig.…”
mentioning
confidence: 99%
“…Alternatively, since no Cyanobacteria were found in our 890 m clone libraries, other bacteria with the same ITS length as cyanobacteria may inhabit the mesopelagic. The depth structure and seasonal patterning of SAR11, and their sister clade AEGEAN-169 (Supplementary Figure S4A, Supplementary Table S4) reflect patterns seen at BATS (Carlson et al, 2009, 11;Vergin et al, 2013a). The seasonality of individual OTUs within the non-seasonal SAR11 Surface 1 clade (Supplementary Tables S4, S5) suggested that this finer resolution is important in understanding the dynamics of this abundant group.…”
Section: Alpha-diversity Patterns Differ Between Depthsmentioning
confidence: 61%
“…In the Sargasso Sea, total Pelagibacterales cell abundances oscillate between 0.5 and 2.2 Â 10 8 cells l À 1 with maximum abundances at or above the pycnocline 40 . Spatiotemporal variation in the distribution of Pelagibacterales ecotypes has been discussed in multiple studies 31,40,41 . The degree to which the presence of C-P lyase genes correlates with the different Pelagibacterales ecotypes and whether the relative abundances of Pelagibacterales-like C-P lyase genes fluctuate seasonally is unknown.…”
Section: Discussionmentioning
confidence: 99%